Dislocated dual HPS between integer and complex fractional order chaotic systems using tracking controllers with application. (24th December 2021) - Khan, Ayub; Trikha, Pushali; Khan, Taqseer
In this article, the dislocated dual hybrid projective synchronisation on two chaotic integer order master systems and two chaotic complex fractional order slave systems is realised. Suitable tracking controllers are designed based on the stability theory of the fractional differential equations. Numerical simulations are performed on complex fractional order Lu system and complex fractional order Lorenz system as slave systems which verify the effectiveness of the tracking control strategy. Comparisons have been made with previously published literature. The application of the designed synchronisation scheme has been applied in the area of secure communication.